Method for preparing sodium battery C-Si negative electrode material by reducing silicon dioxide molecular sieve with hydrogen
The method of preparing sodium-electric C-Si negative electrode material through hydrogen reduction silica molecular sieve solved the problems of high preparation cost, large volume changes, easy structure fracture and fast performance attenuation in the prior art, and achieved a high energy density and uniform pore distribution C-Si negative electrode material, extending the service life of the battery.
Patent Information
- Application Number
- CN202510086415.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
The existing sodium ion battery negative electrode materials have problems such as high preparation cost, large changes in material volume, easy structure to break and fast performance attenuation.
The method of preparing sodium-electric C-Si negative electrode material by hydrogen reduction silica molecular sieve is used to prepare sodium-electric C-Si negative electrode material through ball milling, flotation, pickling, hydrothermal reaction and hydrogen reduction, and the nano-silicon skeleton material is formed and organic carbon is calcined to form C-Si negative electrode material.
The obtained C-Si negative electrode material has high energy density and uniform pore distribution, which can adjust and buffer the volume expansion of silicon, enhance the conductivity of the active material, and extend the service life of the battery.
Smart Images

Figure CN119905561A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery C-Si negative electrode materials, and specifically relates to a method for preparing sodium battery C-Si negative electrode materials by reducing silicon dioxide molecular sieve with hydrogen. Background Art
[0002] Sodium-lithium-ion batteries have similar working principles to lithium-ion batteries and are therefore considered an important alternative to lithium-ion batteries. The patent with publication number CN116487547A discloses a method for preparing silicon-carbon negative electrode materials for sodium-ion batteries; however, this technology requires the addition of silicon sources, which increases costs, and the alloying reaction between silicon and lithium will produce a large volume change. The volume expansion will change the internal structure of the silicon material and cause the material to break; at the same time, the SEI film will break, exposing a new surface, and the SEI film will continue to form on the surface of the broken silicon material fragments, making the SEI film on the surface of the silicon negative electrode unstable.
[0003] In summary, the defects of the existing sodium ion battery negative electrode materials are high preparation cost, large material volume change, easy structure breakage, and rapid performance degradation. Summary of the invention
[0004] In order to overcome the above problems existing in the prior art, the purpose of the present invention is to provide a method for preparing sodium battery C-Si negative electrode material by hydrogen reduction of silica molecular sieve. The negative electrode material obtained by this preparation method has the characteristics of high energy density and uniform pore distribution, and can regulate and buffer the volume expansion of silicon while enhancing the conductivity of the active material.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A method for preparing sodium battery C-Si negative electrode material by reducing silicon dioxide molecular sieve with hydrogen, comprising the following steps:
[0007] Step 1: Mix the coarse gasified slag and the fine gasified slag, then ball mill them, and flot the gasified slag through physical flotation;
[0008] Step 2: Grinding the gasified slag by a sand mill;
[0009] Step 3: Pickling the ground gasified slag to remove basic oxides such as magnesium oxide, calcium oxide, iron oxide, aluminum oxide, etc.
[0010] Step 4: Immerse the acid-washed gasified slag in an alkaline reaction liquid, and prepare a silicon dioxide molecular sieve through a hydrothermal reaction and a template agent;
[0011] Step 5: placing the silicon dioxide molecular sieve in a high temperature furnace for hydrogen reduction, so that the silicon dioxide molecular sieve is reduced into a material with silicon as a skeleton, forming a nano-silicon skeleton material;
[0012] Step 6: Compound the nano-silicon skeleton material with organic carbon to form a nano-silicon organic composite material; and then calcine to form a C-Si negative electrode material.
[0013] In the step 1, the mass ratio of the coarse gasified slag to the fine gasified slag is 3:2-2:3; the components of the coarse gasified slag and the fine gasified slag are shown in Table 1.
[0014] The reason for mixing coarse gasified slag and fine gasified slag is that the coarse slag has a high silicon content, but the silicon extraction rate is lower than that of coarse particles; the fine gasified slag has a relatively low silicon content, but there are few other inorganic substances and it is easy to extract the silicon source. Mixing the two can improve the extraction of the silicon source and a smaller amount of acid and alkali can achieve the extraction purpose.
[0015] The flotation test was carried out in a single-tank flotation machine with a pulp concentration of 80 g / L, a stirring speed of 1600 r / min, and an aeration volume of 0.1 m 3 / L, diesel and secondary glycol are used as collector and foaming agent respectively, the diesel dosage is 30kg / t, and the secondary glycol dosage is 5kg / t.
[0016] The coarse gasified slag contains about 30-35% carbon, the fine gasified slag contains about 40-45% carbon, and the gasified slag with about 60%-80% carbon is floated out.
[0017] The step 2 grinds out gasified slag with a size of 1-10 microns.
[0018] In the step 3, the pickling solution has a mass concentration of 5 to 30 wt%, and the solid-liquid mass ratio of the gasified slag to the hydrochloric acid is set to 2:5-1:10.
[0019] The step 4 is specifically as follows:
[0020] The mass concentration of the alkaline washing solution is 5-10wt%, and the solid-liquid mass ratio of the gasified slag to the sodium hydroxide is 1:3-1:10.
[0021] The template is dissolved in deionized water, and the alkaline solution reaction liquid is gradually dripped into it. Acetic acid is added to adjust the pH to 9-11. After aging for 3 hours, it is transferred to the reactor. The powder is filtered through a hydrothermal reaction, washed to neutrality and then dried, and then the template is removed in an air atmosphere.
[0022] The template agent is selected from hexadecyltrimethylammonium bromide (CTAB) or 1-hexadecyl-3-methylimidazole bromide;
[0023] The concentration of the template solution itself is 0.05M-0.07M, the volume ratio of the alkaline solution reaction solution to the template solution is 1:1-1:1.5, the pH value is adjusted to 7-13, the aging temperature is 30-40°C, the aging time is 1-5 hours, the hydrothermal reaction temperature is 90°C-130°C, the hydrothermal time is 36-96 hours, the drying temperature is 60-100°C, the drying time is 6-24 hours, the temperature for removing the template is 500°C-650°C, and the insulation time is 3-8 hours.
[0024] The silicon dioxide molecular sieve obtained in step 4 has an average pore size of 4 nanometers and a diameter of 200-300 nanometers. The pore size of 4 nm can accommodate the volume expansion of silicon during the charge and discharge process, can better maintain the integrity of the electrode, and extend the service life of the battery.
[0025] In step 5, the temperature of the high temperature furnace is 1200-1400 degrees, and the nano-silicon skeleton material has a one-dimensional hexagonal orderly arranged pore distribution.
[0026] In step 6, the mass ratio of the nano-silicon skeleton material to the organic carbon is 1:19-1:4, and the calcination temperature is 500-1400 degrees.
[0027] The C-Si negative electrode material is a porous carbon-silicon composite material composed of porous silicon and carbon. When the silicon particles change in volume during the charge and discharge process, the pores of the silicon and the surrounding carbon can absorb and disperse this part of the stress, thereby maintaining the integrity of the electrode structure, avoiding the breakage and pulverization of the silicon particles, and improving the cycle stability of the battery.
[0028] The surface of silicon particles of C-Si negative electrode material is covered with a carbon layer, forming a compact secondary particle structure;
[0029] The C-Si negative electrode material has an ordered and uniform hexagonal pore structure, which is connected one by one to form a lotus-like chain, which can provide space for the volume expansion of Si and improve the stability of the material.
[0030] The average diameter of C-Si negative electrode material is between 200-300 nanometers.
[0031] The carbon matrix is composed of carbon materials such as amorphous carbon and organic matter, which are tightly wrapped around silicon particles to form a conductive network. Carbon materials have good conductivity and can provide a fast transmission channel for electrons, thereby improving the conductivity of the entire material.
[0032] Beneficial effects of the present invention:
[0033] In step 2 of the present invention, the gasified slag with a size of 1-10 microns is ground to cause the complex packaging structure of silicate particles in the gasified slag to collapse, so as to more effectively separate and remove the metal oxide components therein.
[0034] In the concentration range of step 3 of the present invention, hydrochloric acid can completely decompose metal oxides such as aluminum oxide and iron oxide contained in the coal gasification slag. At the same time, the solid-liquid ratio ensures that the gasification slag and the hydrochloric acid solution are fully mixed, thereby making the chemical reaction process more uniform and efficient.
[0035] In step 4 of the present invention, the filtrate undergoes a hydrolysis reaction to generate silicic acid, which further undergoes a polycondensation reaction to form oligomers of silicate ions. The template agent CTAB, as a cationic surfactant, forms rod-shaped micelles in water. These micelles provide a template for the polycondensation of silicate ions, guiding the silicate ions to arrange around the micelles to form an ordered mesoporous structure.
[0036] The silica molecular sieve obtained in step 4 of the present invention has an average pore size of about 4 nanometers and a diameter of 200-300 nanometers. The pore size of 4 nm can accommodate the volume expansion of silicon during the charge and discharge process, can better maintain the integrity of the electrode, and extend the service life of the battery.
[0037] The nano silicon-carbon composite material prepared by the present invention has neatly arranged hexagonal mesopores and uniform distribution; both silicon and carbon are nanoscale, which can form a nano synergistic effect; the average diameter of the C-Si negative electrode material is between 200 and 300 nanometers. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a transmission image of the nano-silicon skeleton after reduction of the present invention.
[0039] Figure 2 This is a schematic diagram of XRD of a C-Si negative electrode in Example 1 of the present invention.
[0040] Figure 3 This is a schematic diagram of the cycle of the C-Si negative electrode at 50 mA / g in Example 1 of the present invention.
[0041] Figure 4 This is a transmission image of the C-Si composite material according to Example 1 of the present invention. DETAILED DESCRIPTION
[0042] The present invention will be further described in detail below in conjunction with the accompanying drawings.
[0043] Embodiment 1
[0044] A method for preparing nano C-Si negative electrode material by reducing silicon dioxide molecular sieve with hydrogen, the raw material components and dosage are as follows:
[0045] The concentration of hydrochloric acid is 3M, and the mass ratio of gasified slag to hydrochloric acid is 10:1; the concentration of sodium hydroxide is 2.5M, and the mass ratio of gasified slag to sodium hydroxide is 10:1; the template agent is hexadecyltrimethylammonium bromide; and the organic carbon is residual carbon.
[0046] Preparation process:
[0047] Step 1: After ball milling the coal gasification fine slag for 24 hours, physical flotation is performed to float out the gasification slag with a carbon content of more than 80%.
[0048] Step 2: The gasified slag obtained in step 1 is ground by a sand mill, and the particle size of the obtained gasified slag is 1-10 μm.
[0049] Step 3: react the gasified slag obtained in step 2 with 3M hydrochloric acid at a mass ratio of 1:10 at 80° C. for 4 hours to remove basic oxides such as magnesium oxide, calcium oxide, iron oxide, and aluminum oxide;
[0050] Step 4: react the gasified slag obtained in step 3 with 2.5M sodium hydroxide at a mass ratio of 1:10 at 95° C. for 6 hours, and filter to obtain a filtrate and a filter residue.
[0051] Step 5: Add 0.27 g of hexadecyltrimethylammonium bromide as a template to 15 ml of the filtrate obtained in step 4, perform a hydrothermal reaction at 110° C. for 72 hours, and then calcine at 550° C. in a muffle furnace for 6 hours to obtain a silica molecular sieve.
[0052] Step 6: Introduce hydrogen and nitrogen atmosphere, heat up to 1300°C at a heating rate of 2°C / min and keep warm for 5 hours, reduce the silicon dioxide molecular sieve with hydrogen, and reduce the silicon dioxide skeleton molecular sieve to a material with silicon as the skeleton, forming a nano-silicon skeleton material;
[0053] Step 7: Compound 0.1 g of the nano-silicon obtained in step 6 and 0.5 g of the filter residue (residual carbon) obtained in step 4 by ball milling for 12 hours; then calcine the composite material at a temperature of 1200 degrees to form a composite material with high content of silicon and carbon; and obtain C-Si negative electrode material.
[0054] like Figure 1 As shown, the silicon framework retains the hexagonal pores of the silica molecular sieve after reduction.
[0055] like Figure 2 In the XRD of the C-Si composite material shown, silicon dioxide is reduced to silicon element and is completely composited with the carbon material.
[0056] like Figure 3 The prepared C-Si negative electrode material is cycled at a current density of 50 mA / g, and the decay rate slows down. After 100 cycles, the capacity retention rate is greater than 90%.
[0057] like Figure 4 As shown, the silicon particles are encapsulated in the carbon layer and the pores of the silicon are not filled.
[0058] Embodiment 2
[0059] A method for preparing nano C-Si negative electrode material by reducing silicon dioxide molecular sieve with hydrogen, the raw material components and dosage are as follows:
[0060] The concentration of hydrochloric acid is 3M, and the mass ratio of gasified slag to hydrochloric acid is 10:1; the concentration of sodium hydroxide is 2.5M, and the mass ratio of gasified slag to sodium hydroxide is 10:1; the template agent is hexadecyltrimethylammonium bromide; and the organic carbon is glucose.
[0061] Preparation process:
[0062] Step 1: After ball milling the coarse gasification slag and the fine coal gasification slag for 24 hours, physical flotation is performed to float out the gasification slag with a carbon content of more than 80%.
[0063] Step 2: The gasified slag obtained in step 1 is ground by a sand mill, and the particle size of the obtained gasified slag is 1-10 μm.
[0064] Step 3: react the gasified slag obtained in step 2 with 3M hydrochloric acid at a mass ratio of 1:10 at 80° C. for 4 hours to remove basic oxides such as magnesium oxide, calcium oxide, iron oxide, and aluminum oxide;
[0065] Step 4: react the gasified slag obtained in step 3 with 2.5M sodium hydroxide at a mass ratio of 1:10 at 95° C. for 6 hours, and filter to obtain a filtrate and a filter residue.
[0066] Step 5: Add 0.27 g of hexadecyltrimethylammonium bromide as a template to 15 ml of the filtrate obtained in step 4, perform a hydrothermal reaction at 110° C. for 72 hours, and then calcine at 550° C. in a muffle furnace for 6 hours to obtain a silica molecular sieve.
[0067] Step 6: Introduce hydrogen and nitrogen atmosphere, heat up to 1400° C. at a heating rate of 2° C. / min and keep warm for 5 hours to reduce the silicon dioxide molecular sieve with hydrogen to form a nano-silicon skeleton material;
[0068] Step 7: Compound 0.1 g of nano-silicon obtained in step 6 with 0.5 g of glucose by ball milling for 12 h; then calcine the composite material and carbonize it at 800° C. for two hours under a nitrogen atmosphere to obtain a C-Si negative electrode material.
[0069] Embodiment 3
[0070] A method for preparing nano C-Si negative electrode material by reducing silicon dioxide molecular sieve with hydrogen, the raw material components and dosage are as follows:
[0071] The concentration of hydrochloric acid is 3M, and the mass ratio of gasified slag to hydrochloric acid is 10:1; the concentration of sodium hydroxide is 2.5M, and the mass ratio of gasified slag to sodium hydroxide is 10:1; the template agent is hexadecyltrimethylammonium bromide; and the organic carbon is polyvinyl alcohol.
[0072] Preparation process:
[0073] Step 1: After ball milling the coarse gasification slag and the fine coal gasification slag for 24 hours, physical flotation is performed to float out the gasification slag with a carbon content of more than 80%.
[0074] Step 2: The gasified slag obtained in step 1 is ground by a sand mill, and the particle size of the obtained gasified slag is 1-10 μm.
[0075] Step 3: react the gasified slag obtained in step 2 with 3M hydrochloric acid at a mass ratio of 1:10 at 80° C. for 4 hours to remove basic oxides such as magnesium oxide, calcium oxide, iron oxide, and aluminum oxide;
[0076] Step 4: react the gasified slag obtained in step 3 with 2.5M sodium hydroxide at a mass ratio of 1:10 at 95° C. for 6 hours, and filter to obtain a filtrate and a filter residue.
[0077] Step 5: Add 0.27 g of hexadecyltrimethylammonium bromide as a template to 15 ml of the filtrate obtained in step 4, perform a hydrothermal reaction at 110° C. for 72 hours, and then calcine at 550° C. in a muffle furnace for 6 hours to obtain a silica molecular sieve.
[0078] Step 6: In a hydrogen and nitrogen atmosphere, the temperature is raised to 1200° C. at a heating rate of 2° C. / min and kept for 5 hours to reduce the silicon dioxide molecular sieve with hydrogen to form a nano-silicon skeleton material;
[0079] Step 7: Compound 0.1 g of nano-silicon obtained in step 6 with 0.5 g of polyvinyl alcohol by ball milling for 12 h; then calcine the composite material and carbonize it at 700° C. for two hours under a nitrogen atmosphere to obtain a C-Si negative electrode material.
[0080] Table 1 shows the composition of coarse gasified slag and fine gasified slag
[0081] element C O Si Al other Coarse gasification slag 30.15 38.63 19.89 4.29 7.04 Fine gasification slag 43.32 35.67 9.68 5.67 5.66
Claims
1. A method for preparing sodium battery C-Si negative electrode material by reducing silicon dioxide molecular sieve with hydrogen, characterized in that: The steps include: Step 1: Mix the coarse gasified slag and the fine gasified slag, then ball mill them, and flot the gasified slag through physical flotation; Step 2: Grinding the gasified slag by a sand mill; Step 3: pickling the ground gasified slag; Step 4: Immerse the acid-washed gasified slag in an alkaline reaction liquid, and prepare a silicon dioxide molecular sieve through a hydrothermal reaction and a template agent; Step 5: placing the silicon dioxide molecular sieve in a high temperature furnace for hydrogen reduction, so that the silicon dioxide molecular sieve is reduced to a material with silicon as a skeleton, as a nano-silicon skeleton material; Step 6: Compound the nano-silicon skeleton material with organic carbon to form a nano-silicon organic composite material; and then calcine to form a C-Si negative electrode material.
2. The method for preparing sodium-electrode C-Si negative electrode material by reducing silicon dioxide molecular sieve with hydrogen according to claim 1, characterized in that: In the step 1, the mass ratio of the coarse gasified slag to the fine gasified slag is 3:2-2:3; Fumigation slag with 80%-90% carbon is floated out.
3. The method for preparing sodium-electrode C-Si negative electrode material by reducing silicon dioxide molecular sieve with hydrogen according to claim 1, characterized in that: The step 2 grinds out gasified slag with a size of 1-10 microns.
4. The method for preparing sodium-electrode C-Si negative electrode material by reducing silicon dioxide molecular sieve with hydrogen according to claim 1, characterized in that: In the step 3, the pickling solution has a mass concentration of 5 to 30 wt%, and the solid-liquid mass ratio of the gasified slag to the hydrochloric acid is set to 2:5-1:
10.
5. The method for preparing sodium-electrode C-Si negative electrode material by reducing silicon dioxide molecular sieve with hydrogen according to claim 1, characterized in that: In step 4, the mass concentration of the alkaline washing solution is 5-10wt%, and the solid-liquid mass ratio of the gasified slag to the sodium hydroxide is 1:3-1:10; The template is dissolved in deionized water, and the alkaline solution reaction liquid is gradually dripped into it. Acetic acid is added to adjust the pH to 9-11. After aging for 3 hours, it is transferred to the reactor. The powder is filtered through a hydrothermal reaction, washed to neutrality and then dried, and then the template is removed in an air atmosphere.
6. The method for preparing sodium-electrode C-Si negative electrode material by reducing silicon dioxide molecular sieve with hydrogen according to claim 1, characterized in that: The template agent is hexadecyltrimethylammonium bromide (CTAB) or 1-hexadecyl-3-methylimidazole bromide; The concentration of the template solution itself is 0.05M-0.07M, the volume ratio of the alkaline solution reaction solution to the template solution is 1:1-1:1.5, the pH value is adjusted to 7-13, the aging temperature is 30-40°C, the aging time is 1-5 hours, the hydrothermal reaction temperature is 90°C-130°C, the hydrothermal time is 36-96 hours, the drying temperature is 60-100°C, the drying time is 6-24 hours, the temperature for removing the template is 500°C-650°C, and the insulation time is 3-8 hours.
7. The method for preparing sodium-electrode C-Si negative electrode material by reducing silicon dioxide molecular sieve with hydrogen according to claim 6, characterized in that: The silica molecular sieve obtained in step 4 has an average pore size of 4 nanometers and a diameter of 200-300 nanometers.
8. The method for preparing sodium battery C-Si negative electrode material by reducing silicon dioxide molecular sieve with hydrogen according to claim 1, characterized in that: The temperature of the high temperature furnace in step 5 is 1200-1400 degrees, and the nano-silicon skeleton material has a one-dimensional hexagonal orderly arranged pore distribution.
9. The method for preparing sodium-electrode C-Si negative electrode material by reducing silicon dioxide molecular sieve with hydrogen according to claim 1, characterized in that: In step 6, the mass ratio of the nano-silicon skeleton material to the organic carbon is 1:19-1:4, and the calcination temperature is 500-1400 degrees.
10. A C-Si negative electrode material prepared according to any one of claims 1 to 9, characterized in that: The C-Si negative electrode material is a porous carbon-silicon composite material composed of porous silicon and carbon layers, which reserves buffer space for volume expansion during charging and discharging and relieves the mechanical stress inside the material; The surface of silicon particles of C-Si negative electrode material is covered with a carbon layer, forming a compact secondary particle structure; The C-Si negative electrode material has an ordered and uniform hexagonal pore structure, which is connected one by one to form a lotus-like chain, providing space for the volume expansion of Si. The average diameter of C-Si negative electrode material is between 200-300 nanometers.
Citation Information
Patent Citations
Preparation method of silicon-carbon negative electrode material for sodium-ion battery
CN116487547A
Cited By
Preparation method and application of gasified slag-based carbon-silicon composite material
CN121849965A